The role of partnering and assortative mating by social origin for income inequality: The case of Finland, 1991–2014 - Jani Erola; Elina Kilpi-Jakonen (INVEST Flagship Program, 2025)
Previous studies covering various developed countries suggest that changes in assortative mating by education have contributed only a little to the changes in income inequality, opposite to the expectations of many. In this paper we consider two potential reasons for the zero effects: a) that it is the selection into partnerships rather than assortative mating according to specific characteristics that matters; and b) that for assortative mating to matter, a broader spectrum of matching characteristics than just education should be considered, such as matching by employment and social origin. We study these assumptions using register data on household income inequalities, education, employment and parental class background in Finland 1991–2014. We analyze men and women separately and focus on individuals aged 35–40. We concentrate on between group income inequality as measured by the Theil index. The results suggest that selection into partnership is an important factor behind income inequality and can explain most of the changes in income inequality. Assortative mating does not matter much, even if more sorting characteristics are taken into account. All in all, social origin contributes very little to the income inequality of families in Finland.